2007
DOI: 10.1186/1744-9081-3-13
|View full text |Cite
|
Sign up to set email alerts
|

Determination of hemispheric emotional valence in individual subjects: A new approach with research and therapeutic implications

Abstract: Background: Much has been theorized about the emotional properties of the hemispheres. Our review of the dominant hypotheses put forth by Schore, Joseph, Davidson, and Harmon-Jones on hemispheric emotional valences (HEV) shows that none are supported by robust data. Instead, we propose that individual's hemispheres are organized to have differing HEVs that can be lateralized in either direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 90 publications
2
37
1
Order By: Relevance
“…In contrast to our finding of CGH-R disruption in the maltreated group, another study found reduced FA in the left fusiform gyrus (with projections from cingulum to the posterior tail of the hippocampus) in young adults exposed to parental verbal abuse (Choi et al, 2009). These differences might be attributed to population differences as individual differences exist in hemispheric emotional valence (Schiffer et al, 2007). IFO connects inferior-lateral and dorsolateral frontal cortex with posterior temporal cortex and occipital lobe, and it is involved in emotional visual function.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our finding of CGH-R disruption in the maltreated group, another study found reduced FA in the left fusiform gyrus (with projections from cingulum to the posterior tail of the hippocampus) in young adults exposed to parental verbal abuse (Choi et al, 2009). These differences might be attributed to population differences as individual differences exist in hemispheric emotional valence (Schiffer et al, 2007). IFO connects inferior-lateral and dorsolateral frontal cortex with posterior temporal cortex and occipital lobe, and it is involved in emotional visual function.…”
Section: Discussionmentioning
confidence: 99%
“…Then the computed value for each channel will compared in order to check which brain hemisphere is more active. Based on previous researches that have been done by [58] [59] [56] [57] and [60], the high computed Mean value positively correlated with the more active hemisphere. After computing the mean value for each T7 & T8 pair channel, the difference between each Mean is computed.…”
Section: Variance Of Brain Hemisphere Activitymentioning
confidence: 99%
“…In [55], the experiment of which was to stimulate two classes of emotion of happiness and sadness through the audio-visual stimuli, they stated that the brain activity of left hemisphere recorded a high increase markedly compared with negative emotions. [56] and [57] recognized and classified human emotion based on brain hemisphere activity variance, they determined a new approach for emotion classification based on brain hemisphere activity. Figure 11 illustrates the variance between left frontal lobe and right frontal lobe.…”
Section: Variance Of Brain Hemisphere Activitymentioning
confidence: 99%
See 2 more Smart Citations